Penerapan Komunikasi Politik Cerdas-Bersahabat Melalui Twitter Dalam Membangun Loyalitas Konstituen - Hermawanti, Fritda; Hadiati, Hadiati; sari, Yunita (Jurnal Pustaka Komunikasi, 2023)
This study aims to analyze the application of political communication and constituent responses in response to the implementation of smart-friendly political communication carried out by Mukhammad Misbakhun through social media. This study uses a qualitative research paradigm, which is a constructivism paradigm, a qualitative content analysis approach, and three stages in analyzing data, namely: data collection or data reduction, presentation, and verification or conclusion. The implementation of a political marketing strategy through Mukhammad Misbakhun's Twitter account is carried out by presenting opinion visualizations in the form of videos featuring intellectual rhetoric, posting discussions that are common sense and relevant among the community, and then presenting the figure of Mukhammad Misbakhun as intelligent, namely being able to understand general matters but in detail. The constituent response to the political marketing strategy implemented by Mukhammad Misbakhun was quite enthusiastic, with not many hate speeches. Meanwhile, the response on Mukhammad Misbakhun's Twitter account still has a gap between the number of followers and the number of likes, comments, and retweets, except for one video about appreciation to the Directorate General of Taxes.